1994
DOI: 10.1172/jci117036
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vascular smooth muscle cell proliferation in vitro and in vivo by c-myc antisense oligodeoxynucleotides.

Abstract: Restenosis after angioplasty is due predominantly to accumulation of vascular smooth muscle cells (VSMCs). The resistance of restenosis to pharmacological treatment has prompted investigation of genes involved in VSMC proliferation. We have examined the effect on VSMC proliferation of blocking expression of the c-myc proto-oncogene with antisense oligodeoxynucleotides, both in vitro and in a rat carotid artery injury model of angioplasty restenosis. Antisense c-myc oligodeoxynucleotides reduced average cell le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
2

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(91 citation statements)
references
References 32 publications
2
87
2
Order By: Relevance
“…To determine the temporal pattern with which E11 associates with SMCs, the PS-ODN was 5Ј end-labeled with 32 P by kinase reaction and incubated with the cells for various times. 32 P-E11 was taken up most efficiently within the first 4 hours of exposure and optimally after 6 hours ( Figure 3).…”
Section: P-labeled E11 By Smcsmentioning
confidence: 99%
“…To determine the temporal pattern with which E11 associates with SMCs, the PS-ODN was 5Ј end-labeled with 32 P by kinase reaction and incubated with the cells for various times. 32 P-E11 was taken up most efficiently within the first 4 hours of exposure and optimally after 6 hours ( Figure 3).…”
Section: P-labeled E11 By Smcsmentioning
confidence: 99%
“…remained constant at 30 to 50%, despite drug regimens Many protocols involving cationic liposomes for the which have been used in an attempt to control it. 1,2 The delivery of DNA, [16][17][18][19]21 or antisense oligonucleoexact cause of restenosis remains controversial, although tides 11,12,22 into cells and tissues have been described in the migration and overproliferation of vascular smooth vitro and in vivo. 23 Indeed, the protocols have progressed muscle cells (VSMCs) and simultaneous production of to the point where a number of human gene therapy extracellular matrix have been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…Antisense oligonucleotides targeted against c-myc and c-myb have been reported to result in reduced c-myc and c-myb protein levels and inhibition of proliferation of human and rat VSMCs in vitro. [16][17][18][19] Similarly, in vivo transfection studies utilizing antisense c-myc and c-myb oligonucleotides have reported reduced c-myc or c-myb expression and reduced neointimal thickening following vascular injury in a number of animal models. 16,[20][21][22] However, therapeutic application of antisense oligonucleotides is hampered by cellular uptake and stability, as well as by their lack of cell-and possibly target mRNA-specificity.…”
mentioning
confidence: 99%
“…[16][17][18][19] Similarly, in vivo transfection studies utilizing antisense c-myc and c-myb oligonucleotides have reported reduced c-myc or c-myb expression and reduced neointimal thickening following vascular injury in a number of animal models. 16,[20][21][22] However, therapeutic application of antisense oligonucleotides is hampered by cellular uptake and stability, as well as by their lack of cell-and possibly target mRNA-specificity. [23][24][25][26] Consequently, antisense gene expression vectors containing the c-myc cDNA have been created and shown to reduce cmyc expression and cellular proliferation in a number of cell types.…”
mentioning
confidence: 99%